Review of Nondestructive Testing Methods for Condition Monitoring of Concrete Structures. (4th April 2013) - Verma, Sanjeev Kumar; Bhadauria, Sudhir Singh; Akhtar, Saleem
Abstract : The deterioration of concrete structures in the last few decades calls for effective methods for condition evaluation and maintenance. This resulted in development of several nondestructive testing (NDT) techniques for monitoring civil infrastructures. NDT methods have been used for more than three decades for monitoring concrete structures; now it has been recognized that NDT plays an important role in the condition monitoring of existing RC structures. NDT methods are known to be better to assess and evaluate the condition of RC structures practically. This paper reviewed several available NDT methods developed and used in the last few decades.